IMPLEMENTASI KEBIJAKAN TRIPLE SKILLING DALAM MEMBANGUN SUMBER DAYA MANUSIA TERAMPIL DAN PRODUKTIF (STUDI KASUS: BALAI BESAR PENGEMBANGAN LATIHAN KERJA BEKASI) - Fauzi, Syifa; Laksmono, Bambang Shergi (UI Scholars Hub, 2021)
The development of skilled and productive human resources is one of the main priorities of President Joko Widodo's policy. The unemployment burden which continues to increase due to the emergence of mismatches of workers' skills with company needs and automation will be a threat to the future of the workforce in Indonesia. The Triple Skilling Policy (Skilling, Re-skilling, Up-skilling) were made to minimize labor problems in Indonesia. Balai Besar Pengembangan Latihan Kerja Bekasi as one of the vocational training centers that conducts job training has implemented a Triple Skilling policy in 4 vocations which are Electronic Engineering, Refrigeration, Information and Communication Technology, and Tourism. The purpose of this research is to determine the implementation of the Triple Skilling policy in BBPLK Bekasi and the benefits of the policy in building competent and productive human resources. This study used a qualitative approach with data collection using direct observation techniques and in-depth interviews with head of the training program section, instructors, and training participants at BBPLK Bekasi. Through the implementation, several problems were encountered, such as the short duration of training, the diversity of educational backgrounds and skills of training participants, and the need to improve the competence of instructors at BBPLK Bekasi.